Wildfire Dynamics and Occasional Precipitation during Active Fire Season in Tropical Lowland of Nepal - Bhujel, Krishna Bahadur; Byanju, Rejina Maskey; Gautam, Ambika P.; Mandal, Ram Asheshwar (Environment and Natural Resources Journal, 2017)
Occasional precipitation plays a vital role in reducing the effect of wildfire. This precipitation is especially important for countries like Nepal, where wildfires are a common seasonal event. Approximately 0.1 million hectare of forest area is affected annually due to wildfires in active fire season. The study on the relation of these forms of occasional precipitation with wildfire incidence is still lacking. This research was objectively carried out to examine the correlation of occasional precipitation with wildfire incidence and burnt area. The Moderate Resolution Imaging Spector-Radiometer (MODIS) satellite images and precipitation records for 15 years gathered from Department of Hydrology and Metrology were used as input data for this study. The images were analyzed by using ArcGIS function while the precipitation records were analyzed by using Statistical Package for the Social Science (SPSS) program. The linear regression model was applied to find correlation of occasional precipitation with wildfire incidence and burnt area. Analysis revealed decreasing trend of precipitation in study area. We found significant correlation (p<0.05) of precipitation with wildfire incidence and burnt area. Findings will be useful for policy makers, implementers and researchers to manage wildfire in sustainable basis